Perancangan Pembelajaran Fisika Menggunakan Multimedia Interaktif untuk Meningkatkan Minat Mahasiswa terhadap Mata Kuliah Fisika - Marvin Chandra Wijaya (SPEJ (Science and Physic Education Journal), 2019)
This study aims to measure the increased interest of students in the Maranatha Christian University Computer Systems Study Program in Physics Subjects. The increase in interest uses interactive multimedia-based learning systems. The learning system is designed using the SMIL (Synchronized Multimedia Interactive Language) programming language. The physics course learning system designed in this study is course material about Object Motion (Regular Straight Motion / GLB, Irregularly Changed Straight Motion / GLBB, Free Falling Motion / GJB, Vertical Upward Motion / GVA, Vertical Down Motion / GVB) . Thirty students were taken as samples to see interest in Physics courses. Data retrieval is taken before and after the provision of learning materials using interactive multimedia. The average value of interest in Physics Subjects before the use of interactive multimedia learning materials was 7.12 on a scale of 10, increasing to 8.57 after the use of interactive multimedia learning materials. Hypothesis testing uses paired t test. The results of statistical processing showed a significant increase in student interest in Physics. Keywords: Physics Learning, Interactive Multimedia, SMIL, Object Motion